Generalized Parameter and Compatibility factor of Thermoelectric n-SixGe1-x - Nakhutsrishvili, I. (Journal of Thermoelectricity, 2025)
The dependence of the maximum of the figure of merit (ZT)max of the SixGe1-x alloy on the generalized parameter of material B* is investigated. A formula is used to calculate the values of B*, which contains the quantities of band gap, specific electrical conductivity, scaled parameter and lattice thermal conductivity: B* ≅ 7.755·10-4Eg kL-1. This formula is derived from the combination of the formulas known from the literature that relate the thermoelectric parameters - mobility, effective mass and weighted mobility of charge carriers. This formula no longer includes effective mass, mobility and temperature - these parameters are replaced by specific electrical conductivity and the Seebeck coefficient. Dependence (ZT)max – B* is constructed. By calculating the generalized parameter, you can approximately estimate the maximum value of the figure of merit for almost any thermoelectric. The compatibility factor of SixGe1-x has been determined. The possibility of creating segmented thermogenerators based on this material in combination with YbMg1.8Zn0.05Bi1.98, CuAl0.8Fe0.2O2 and Cu1.98S is indicated.